Pelatihan Online Marketing Pada Pelaku UMKM Olahan Makanan - Pamela Pamela; Nurliza Nurliza (Indonesian Journal Publisher, 2024)
Online marketing is a set of tools and methodologies used to promote products and services over the internet. Online marketing includes broader marketing elements than traditional business marketing because of the extra channels and marketing mechanisms available on the internet. Online marketing is also known as marketing using the internet, web-based marketing, and digital marketing. Community service activities aim to increase the number of research outputs and community service per lecturer, which have succeeded in gaining international recognition or been implemented by the community (IKU 5). The solution for improving processed food MSMEs related to online marketing is carried out using counseling and demonstration (Practice) methods. Marketing management regarding online marketing in question is knowledge about online marketing, techniques for managing grammar in online marketing, and online marketing evaluation techniques. This activity includes counseling and technical guidance packaged in the form of online marketing knowledge and skills. The number of participants who will take part in the training is 10 people at UMKM Chef Gui in Pontianak. The stages of implementing Community Service consist of planning, field observation, preparation, implementation of training, evaluation and monitoring, reporting and dissemination of the results of Community Service Activities. Conclusion: The community service activities carried out went well. Chef Gui's Food Processed MSME employees received increased knowledge (75 percent) regarding online marketing for Community Service.